Comparison of Portfolio Selection and Performance: Shari’ah-Compliant and Socially Responsible Investment Portfolios - Asutay, Mehmet; Hendranastiti, Nur Dhani (The Indonesian Capital Market Review, 2015)
This study examines the effect of Islamic screening criteria on Shari’ah-compliant portfolio selection and performance compared to Socially Responsible Investment (SRI) portfolio. Each portfolio constructed from 15 stocks based on FTSE 100 using data from year 1997. Mean-variance portfolio optimization is employed with some financial ratios added as constraints for the Shari’ah portfolio. Annual expected return of each portfolio from 2008 to 2013 is used to calculate Sharpe’s ratio, Treynor ratio and Jensen’s alpha as the performance measurement tools. Macroeconomic variables are assessed using ordinary least square to examine whether they influence the portfolios’ expected returns or not. The result finds that Shari’ah portfolio has a better performance than SRI from year 2008 to 2010 shown by higher value of the measurement tools. However, from 2011 to 2013, SRI portfolio has better performance than Shari’ah portfolio.